Hattin - France, John (Oxford University Press, 2015)
On 4 July 1187 the legendary Muslim leader Saladin destroyed the Crusader army of the Latin Kingdom of Jerusalem with a terrible slaughter at the battle of Hattin - and went on to restore the Holy City of Jerusalem to Islamic rule. In this new volume in the 'Great Battles series', John France analyses the origins and course of this pivotal battle, illuminating the roots of the bitter hatred which underlay it, and explains its significance in world history - from medieval times to the present.